Determinants of Adolescent Health Service Use Evidence from X Community Health Center in Semarang City - Budiyono, Shabrina Putri; Arso, Septo Pawelas; Budiyanti, Rani Tiyas (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: “X” Community Health Center provides adolescent health services, including counseling, information, education, and an integrated adolescent health post. However, adolescent participation in this program remains very low, at only approximately 1.57%. The purpose of this study was to analyze the determinants of adolescent health service utilization in a Community Health Center working area.Methods: Cross-sectional quantitative research was carried out in the “X“ Community Health Center working area between November 2024 and February 2025. One hundred and two participants constituted the research sample, and the sample division employed clustered random sampling and the accidental sampling technique to obtain data. Data analysis was performed using the chi-squared test and Andersen's health service utilization theory.Results: In total, 54.9% of the adolescents did not optimally utilize health services. The determinants of adolescent health services were gender (p=0.025), knowledge (p=0.031), attitude (p=0.000), peer support (p=0.000), support from health workers (p=0.000), and access to information (p=0.000).Conclusion: Female, who had good knowledge, had peer and health workers’ support, and good access of information tended to use adolescent health services. Forming peer mentors to increase adolescent motivation, using educational media, and organizing interesting service programs, as well as disseminating information through “X“ Health Center social media